PEMBERIAN BANTUAN PROGRAM KELUARGA HARAPAN SEBAGAI AMANAT KONSTITUSI PERSPEKTIF SIYASAH SYAR’IYYAH - Tayang, Riswandi; Sastrawati, Nila; Syatar, Abdul (Prodi Hukum Tata Negara (Siyasah Syariyyah) Fakultas Syariah dan Hukum UIN Alauddin Makassar, 2023)
This study aims to analyze the implementation of Program Keluarga Harapan assistance based on the constitutional mandate of the siyasah syar'iyyah perspective. The type of research used is qualitative field research with a normative shari'i and empirical juridical approach. The results showed that the mechanism for providing assistance for the Program Keluarga Harapan in Makassar City was carried out systematically starting from determining the location and number of prospective beneficiary families, determining beneficiary criteria, implementing socialization and data validation processes, implementing commitment verification, implementing family hope program assistance and updating data. Program Keluarga Harapan assistance in Makassar City is given in the form of money distributed through four stages a year, non-cash distribution disbursed through the Kartu Keluarga Sejahtera. In the concept of siyasah syar'iyyah, the Program Keluarga Harapan contains the principle of ta'awun (help) but in the relationship between the government and its people to meet the needs of the dharuriyat; Primary such as food and secondary needs (hajiyat) namely education and health.